A comprehensive analysis of corneal mRNA levels during sulfur mustard induced ocular late pathology in the rabbit model using RNA sequencing. (July 2019) - Horwitz, Vered; Cohen-Gihon, Inbar; Egoz, Inbal; Dachir, Shlomit; Cohen, Maayan; Cohen, Liat; Gutman, Hila; Gez, Rellie; Kadar, Tamar; Gore, Ariel; Beth-Din, Adi; Zvi, Anat; et al.
Abstract: Exposure to sulfur mustard (SM) may result in severe ocular injuries. While some of the eyes show a clinical resolution of the injury (defined as clinically non-impaired), part of the eyes develop irreversible late ocular pathologies (defined as clinically impaired) that may lead to corneal blindness. Understanding the pathological mechanisms underlying the development of the late pathology may lead to improved treatment options. Therefore, this study aimed to investigate the mRNA expression profiles of corneas from clinically impaired, clinically non-impaired and naïve eyes. Rabbit eyes were exposed to SM vapor and a clinical follow-up was carried out up to 4 weeks using a slit lamp microscope. At this time point, corneal tissues from clinically impaired, clinically non-impaired and naïve eyes were processed for RNA sequencing (RNA-seq) and differential expression analyses. The differential expression profiles were further subjected to pathway enrichment analysis using Ingenuity Pathway Analysis (IPA). Real-time PCR was used for RNA-seq validation. The late pathology developed in 54%–80% of the eyes following ocular exposure to SM, clinically manifested by inflammation, corneal opacity and neovascularization. RNA-seq results showed significant differences in mRNA levels of hundreds of genes between clinically impaired, clinically non-impaired and naïve corneas. Pathway enrichment analysis showed common pathways that were activated in all of the exposed eyes, such as Th1 and Th2 activation pathway, in addition to pathways that were activated only in the clinically impaired eyes compared to the clinically non-impaired eyes, such as IL-6 and ERK5 signaling. Corneal mRNA expression profiles for the clinically impaired, clinically non-impaired and naïve eyes generated a comprehensive database that revealed new factors and pathways, which for the first time were shown to be involved in SM-induced late pathology. Our data may contribute to the research on both the pathological mechanisms that are involved in the development of the late pathology and the protective pathways that are activated in the clinically non-impaired eyes and may point out towards novel therapeutic strategies for this severe ocular injury. Highlights: mRNA expression profiles for corneas during sulfur mustard induced late pathology were generated. New factors and pathways were suggested to contribute to the development of the late pathology. The presented data may point out towards pathological and protective mechanisms in sulfur mustard exposed eyes.